UJI AKTIVITAS ANTIOKSIDAN SEDIAAN SABUN CAIR DARI EKSTRAK KULIT SINGKONG (Manihot esculenta Crantz) - Sukmawati; Ihwanudin Subagja, Ilham; Tantri , Elisa (LP4M STIKes Karsa Husada Garut, 2025)
Introduction: Cassava peels contain phenolic compounds such as tannins, flavonoids that act as antioxidants that can inhibit free radical activity. The purposeof this study was to make a liquid soap formulation from cassava peel extract and determinate the most powerful antioxidant levels contained in the liquid soap formula. Method includes experimental research by making several formulas of cassava peel extract liquid soap preparations with concentrations of 5%, 10%, and 15%, then conducting physical evaluation tests and antioxidant activity test using Uv-Vis spectrophotometry. Result: The test results were described in tabular form and analyzed with One Way ANOVA statistics followed by post hoc (LSD) to find differences in the percentage of antioxidant activity from various concentrations. The results of antioxidant activity research from the three formulas have IC50 values FI (5%) 96,415 ppm (strong), FII (10%) 101,774 ppm ( medium), and FIII (15%) 101,322 ppm (medium). The amount of concentration in each formula affects the amount of antioxidant activity in it. The results of the One Way ANOVA test obtained a significance value of (p<0,001) which shows that there is a difference in antioxidant activity in each formula. Conclusion. this study is that cassava peel extract can be formulated into antioxidant liquid soap preparations but has not met the standards of physical quality stability of good preparations and the highest antioxidant activity is found in FI (5%) at 96, 415 ppm.